(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The power take off for wave energy remains one of the key technical challenges that must be overcome before technical maturity. The low speed reciprocating nature of many devices combined with the challenging environment require the development of bespoke electrical machines in a direct drive system. This paper describes a research project that is developing a small direct drive wave energy device. The aim is to prove that electrical machines can reliably operate in the marine environment. Heaving buoys are wave energy converters where power is extracted by applying a force to oppose the vertical motion of a floating or submerged prime mover. The force is applied by the power take off which requires provision of an inertial reference, for example a drag plate or the sea bed. Linear direct drive power take off in heaving wave energy converters can suffer from end stop problems, where large uncontrolled oscillations and forces between the prime mover and the inertial reference damage the power take off. For example, over extending either a hydraulic or electric power take off in storm waves off can cause irreconcilable damage. One way of avoiding this is to remove the inertial reference in rough seas. In an IPS buoy the inertial reference is provided by a piston coupled to water entrapped by an open ended cylinder. If the piston leaves the cylinder, it is no longer coupled to the water mass and its inertial reference drastically reduces. In this case the piston can simply ‘follow’ the prime mover oscillation. An IPS buoy therefore presents an excellent device to demonstrate direct drive power take off. In the direct drive demonstrator proposed in this paper, the electrical power take off is integrated with the inertial piston and tube of an IPS buoy. The piston acts as the electrical translator and the cylinder houses the stator coils. A number of design challenges are presented. For example, the piston/translator either needs to be neutrally buoyant, or must be held in position by an external force. Neutral buoyancy imposes constraints on the size and solidity of the translator, whereas the length and radius of the cylinder directly effects the amount of power that can be captured. It is an integrated design problem. A hydrostatic model to size the piston and a linear hydrodynamic model to size the cylinder are presented. The active area of the electric power take off is constrained by the parameters of the piston and cylinder, so design requires integrated hydrostatic, hydrodynamic and electromagnetic modelling. Oscillation results are compared to predictions from commercial software for validation and used to inform the electrical design. The electrical generator will oscillate slowly compared to conventional generators implying the use of some form of magnetic gearing, challenging for mass constrained designs, or reliance on a large amount of rare earth magnetic materials, which has a significant cost implication. A number of electrical machine topologies are investigated in the paper (surface mounted PM machines, Halbach array, and flux concentrated).